Children's and juvenile tales: a playful practice of humanization for hospitalized children - Elaine Cristina Rodrigues Gesteira; Elaine Cristina Dias Franco; Patrícia Pinto Braga; Maria Beatriz Rodrigues Criscuolo; Jéssica Silva Oliveira (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769212071 Objective: to understand the reactions of hospitalized children and their families as they listen to children's stories during the activities of the research and extension project: "Children's and Juvenile Tales: an interface with the humanization of care in hospital". Method: this is a descriptive and qualitative study which used the observational method. Twelve children in hospital and their families participated in the study. Data were collected from participant observation and field record and then analyzed, giving rise to three categories. Results: there was evidence that children have different reactions while listening to  the stories, such as changes in mood, body language and facial expressions. Furthermore, it was noticed that the hospitalized child's family appreciates this playful practice as a moment of joy and enthusiasm. Conclusions: the study reveals the need for playful practices that humanize the pediatric environment and assist the child and their family in the hospitalization.